IMPLEMENTASI PROSES BELAJAR PAI DI SMP ALKHAIRAAT TOLIBA - Nurmaya Medopa (Fakultas Keguruan dan Ilmu Pendidikan, 2020)
This research includes implementation, implications, supporting factors, obstacles to the implementation of Islamic Religious Education learning at Alkhairaat Toliba Middle School. The research used a qualitative approach based on field research, the research data were collected through observation, interviews, documentation, analysis, reduction, presentation, and data levers. The results of the study found that: The implementation process of learning Islamic religious education at SMP Alkhairaat Toliba includes curriculum evaluation, evaluation process, the concept of KTSP, creating a religious culture as an implementation of the learning process. The implication of the learning process of Islamic Religious Education in increasing the religious understanding of students at Alkhairaat Junior High School in Toliba Village has a positive effect on increasing students' understanding above the standard of completeness of the Islamic Religious Education learning process. Supporting factors; the ability of teachers, provision of teaching aids / learning media, support for madrasah principals and staff. The inhibiting factors are: a picture of limited time to study Islamic Religious Education, difficulties in dealing with the character of students